KETAHANAN PANGAN MASA PANDEMI COVID-19 MELALUI HYDROPONIK DALAM SKALA RUMAH TANGGA DI KELURAHAN KEDUNG BARUK KECAMATAN RUNGKUT SURABAYA - Tukiman Tukiman; Bayu Aditya Pratama Putra; Isna Meydiawati; Anisa Rachmawati (Jurnal Penelitian Administrasi Publik, 2020)
The spread of the Covid-19 virus allows people to reduce their activities or activities related to outside the home in order to reduce the spread of the virus. The development of science such as hydroponic growing media is very helpful for household scale that does not have vacant land to grow crops so that even narrow land can be used to grow other than that it can meet food needs. Hydroponics with a wick system are recommended for beginners because the basic principle is only to use water capillarity, in addition it does not require special maintenance, is easy to assemble, portable (can be moved), and is suitable in limited areas. Besides that guaranteed crop freedom from pests and diseases, plants grow faster and use of fertilizers more economically. The existence of this article is expected to be able to educate the public, especially in the village of Kedung Asem in terms of growing the hydroponic system to meet household scale food needs while in this pandemic. Keywords : Hydroponic, Covid-19, Wick System